The Red Door Inn [large type] - Johnson, Liz, 1981- (Johnson, Liz, 1981- Prince Edward Island dreams, 2016)
Broke and desperate, Marie Carrington is hoping to find safety and sanctuary on Prince Edward Island, where she reluctantly agrees to help decorate a renovated bed-and-breakfast before it opens for prime tourist season. Seth Sloane didn't move three thousand miles to work on his uncle's B&B so he could babysit a woman with a taste for expensive antiques ; he came to help restore the old Victorian-- and to forget about the fiancée who broke his heart. Can these two wounded souls find hope, healing, and perhaps a bit of romance on this beautiful island?